The Effect of Strategic Awareness on Creative Performance an Analytical Study of The Opinions of Faculty Members at A University Level - Kazem, Jassim Rahi; Abbas, Yasir Abdullah; Sabti, Yousif Mousa; Ali, Ghazanfar; Nasser, Raed Hamid (South Asian Journal of Social Sciences and Humanities, 2022)
The current research focused on the correlation and impact between the strategic awareness with its dimensions (expanded awareness, filtering and sensory awareness, human experience, and mental awakening) and the creative performance represented by its dimensions (idea generation, idea promotion, and idea application). The research used a questionnaire with internationally controlled standards as a main tool for data collection. The questionnaire forms were distributed to a sample of (60) teachers distributed over (5) colleges at the University of Al-Muthanna. The research reached several conclusions, including the existence of a significant positive correlation a statistic of the dimensions of strategic awareness collectively and individually in each of the dimensions of creative performance and the relationship of impact in different proportions. It also became clear that the sample members have a desire to have interest from college administrations in rewarding individuals Lead the creators and overcome obstacles to exchange opinions, ideas and information that will enable them to develop themselves and thus their faculties through achieving qualitative innovations. The research recommends that university leaders investigate the best means to attract individuals with high qualifications and develop mechanisms to attract and retain them, and twinning between universities and international organizations in order to raise the creative capabilities of teaching staff.